The problem of domestic violence in professional practice nurses and midwives - Agnieszka Konstancja Pawłowska-Muc; Celina Łepecka-Klusek; Grażyna Stadnicka; Anna Bogusława Pilewska-Kozak; Beata Dobrowolska; Klaudia Pałucka (Kazimierz Wielki University, 2017)
Introduction. Medical staff, including nurses and midwives, should play a significant role   in recognizing violence, its forms and victims. Aim of the study. Verify that the course of their professional nurses and midwives are in contact with victims of domestic violence and then they take action. Material and methods. The study included 295 nurses and midwives, participating in one of the forms of postgraduate education - specialist education or specialized course in your chosen field. The research was conducted in November and December 2015 the Center for Postgraduate Education of Nurses and Midwives in Radom and Lublin. The criterion for inclusion in the group of respondents was an agreement to participate in them. The study used diagnostic survey method using a questionnaire of our own design. The collected material was analyzed by descriptive and statistical, using computer software IBM SPSS (version 21). Research results. Most of the respondents (241; 81.7%) stated that during the execution of work had been in contact with victims of domestic violence, with significantly more so than claimed a nurse midwives (p <0.001). Among the forms of which were met, it was as often physical and mental violence. Further neglect, economic and sexual violence. The perpetrators were most often men (husbands, partners) and the victims women. Nurses and midwives have taken a total of 232 interventions against those abused. The dominant activity was to inform the police and the social welfare center. Conclusions. 1. Contact with victims of domestic violence have the majority of working nurses and midwives, some of them more than once. 2. Interventions nurses and midwives, to  people experiencing domestic violence, rely mainly on the problem is reported to the police or a social welfare center.